Estimation of Carbon Stock Stands using EVI and NDVI Vegetation Index in Production Forest of Lembah Seulawah Sub-District, Aceh Indonesia - Jhon Pandapotan Situmorang; Sugianto Sugianto; Darusman . (Aceh International Journal of Science and Technology, 2016)
This study aims to determine the distribution of the vegetation indexes to estimate the carbon stocks of forest stands in the Production Forest of Lembah Seulawah sub-district. Aceh Province, Indonesia. A non-destructive method using allometric equations and landscape scale method were applied, where in carbon stocks at the points of samples are correlated with the index values of each transformation of the vegetation indexes; EVI and NDVI.  Results show that EVI values of study area from 0.05 to 0.90 and NDVI values from 0.17 to 0.85. The regression analysis between EVI with carbon stock value of sample locations equation is Y = 151.7X-39.76. with the coefficient of determination (R2) is 0.83. From this calculation, the total carbon stocks in the Production Forest area of Lembah Seulawah sub-district using EVI is estimated 790.344.41 tonnes, and the average value of carbon stocks in average is 51.48 tons per hectare.  Regression analysis between NDVI values at the research locations for the carbon stack measured samples is Y = 204.Xx-102.1 with coefficient of determination (R2) is 0.728. Total carbon stocks in production forest of Lembah Seulawah sub-district using NDVI is estimated 711.061.81 tones. and the average value of carbon stocks is 46.32 tons per hectare. From the above results it can be concluded that the vegetation indexes: EVI and NDVI are vegetation indexed that have a very close correlation with carbon stocks stands estimation. The correlation between EVI with carbon stock and the correlation between NDVI with carbon stock is not significantly different